THE EFFECT OF REMUNERATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT PT. ASKRIDA SYARIAH INSURANCE MEDAN BRANCH - Muhammad Andre Alkahfi; Sri Ramadhani (istinbath, 2023)
In developing the company, the factors of employee performance are crucial to note; the factor of employee discipline to comply with applicable regulations and the remuneration provided by the company can be seen through attitudes that influence performance achievement with better work results. In this study, the authors conducted research at PT. Askrida Syariah Insurance Medan Branch. This study's methodology combines a quantitative research approach and an explanatory research approach. The population in this study were all employees of PT. Askrida Syariah Insurance Medan Branch has as many as 30 employees, and the data needed is personal data and respondents' views (questionnaire) on remuneration variables, work discipline and employee performance. This study didn't find any real connection between employee remuneration and performance, and the significance value was above 0,111 > 0.05. The significance of work discipline on employee performance was clearly demonstrated by a f- test with a significance value of 0.000 < 0.05. This indicates that both remuneration and work discipline are essential factors for good performance at PT Askrida Syariah Insurance Medan Branch. Around 82% of differences in employee performance can be attributed to differences in the independent variables. The other 18.2% is made up of things that weren't part of this study.